2008
DOI: 10.1016/j.saa.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational group frequency of the N–O stretching band of nitroxide stable free radicals

Abstract: cm -l for 6-membered cyclic and acyclic nitroxides. In nitronyl nitroxides, the symmetric 2 stretching vibration occurs in the region 1470 cm -1 , but coupling to other modes makes specific band assignments problematic for the nitronyl nitroxide group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
5
39
0
1
Order By: Relevance
“…The cross sections in Figure 4 show that electron collisions with TEMPO excite primarily the N−O stretch, the C−H stretch, and the N-pyramidalisation vibrations. (The N−O stretch vibration was reported at 166 meV [54], but our B3LYP calculations indicate four vibrations with a pronounced N−O stretch motion in the range 170-180 meV and more than one of these vibrations appear to be excited by electron impact, leading to a broadened EEL band peaking at 177 meV. Our cross section applies to this entire band.)…”
Section: Negative Ionmentioning
confidence: 62%
“…The cross sections in Figure 4 show that electron collisions with TEMPO excite primarily the N−O stretch, the C−H stretch, and the N-pyramidalisation vibrations. (The N−O stretch vibration was reported at 166 meV [54], but our B3LYP calculations indicate four vibrations with a pronounced N−O stretch motion in the range 170-180 meV and more than one of these vibrations appear to be excited by electron impact, leading to a broadened EEL band peaking at 177 meV. Our cross section applies to this entire band.)…”
Section: Negative Ionmentioning
confidence: 62%
“…With size exclusion chromatography (SEC), we showed an increase in molecular weight after ligation for all polymers, while IR (ESI † ) clearly showed a vibration at 1350 cm –1 , which is indicative for a nitroxide vibration. 12 Peaks at 1640 cm –1 and 1450 cm –1 are indicative for triazole ring vibrations. 13 Also, in P2 , peaks at 1660 cm –1 and 1540 cm –1 are indicative for the carbonyl vibration and amide II vibration originating from the presence of the amides of benzene-1,3,5-tricarboxamides.…”
mentioning
confidence: 99%
“…In Figure 3(b), the powder spectrum after treatment with solvent to obtain crystals of II, was similar to the spectrum of III, showing broad bands between 2852-2620 cm -1 , which are attributed to hydrogen bonds due to N−OH … or to quaternary amino groups (R 2 N + H−). It was important to verify the frequencies, specifically the presence of the functional group N + =O, because for compound 1, an experimental vibrational stretching at 1614 cm -1 had been reported [30,39], which indicated that the value differed widely from the theoretical calculation. Therefore, in Table 2, we presented the vibrational frequencies of the optimized structures of TEMPO, I, II and III calculated in gas and including the solvent effect of CCl 4 (ε=2.2280) and n-hexane (ε=1.8819) by using the SCRF method with a Polarizable Continuum Model (PCM) [40].…”
Section: Resultsmentioning
confidence: 99%
“…,♦,•] ♣experimental values[30]; ♦calculated values[30]; • calculated values[39]. frequencies in (cm -1 ) of the optimized structures TEMPO, I, II and III in gas phase and in CCl 4 and n-hexane solvent phases.…”
mentioning
confidence: 99%